Postexposure Pestes-des-petits-ruminants vaccination with oxytetracycline therapy mitigates severe disease and increases survivability in natural infections - Ezeasor, C; Shoyinka, S; Emikpe, B; Ihedioha, J (Journal of the Hellenic Veterinary Medical Society, 2024)
The potentials of post-exposure intranasal (IN) and subcutaneous (SC) Peste des petits ruminants vaccination (PPRVc) with concurrent oxytetracycline (oxytet.) treatment in the management of PPR outbreaks in goats were investigated. Twenty-eight (28) West African dwarf goats, were randomly assigned into 7 groups: A (Oxytet.), B (IN - PPRVc), C (IN-PPRVc + Oxytet.), D (SC-PPRVc), E (SC-PPRVc + Oxytet.), F (Infected, untreated control), and G (Normal control). Natural PPRV infection was induced by the co-habitation method and following the onset of pyrexia in 75% of the goats, the interventions were administered accordingly. The leukocytic profiles were evaluated on days 1, 3, 5, 7 and 14 post-intervention (p.in). The clinical scores (CS), mortality pattern, lung lesion scores (LLS) and pathology were also evaluated post-intervention. A survivabilty score of 50% was observed in groups C and E with clinical scores of 2.06 and 3.90, while 100% mortality was recorded in the other groups with clinical scores of 4.38, 5.89, 7.05 and 6.92, for groups A, B, D and F, respectively. A mild decrease in the total leukocyte counts and absolute lymphocytes counts was observed in all the PPRV exposed groups by day 3 through 5 p.in but increased significantly (p<0.05) in groups C and E by day 14 p.in. Also, groups C and E showed the least mean (s.e.m) lung lesion scores of 0.61(0.12) and 0.64(0.15), respectively and also showed a relatively normal pulmonary, illeal, splenic and lymph node histomorphology, compared to the other groups. Postexposure PPR vaccination with concurrent oxytetracycline therapy significantly altered the known clinicopathology of PPR in goats, mitigated the disease severity and resulted in higher survivability in natural PPR infection.